2005
DOI: 10.1111/j.1600-0404.2005.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental light-dark changes on experimental mild traumatic brain injury

Abstract: Following MTBI light deprivation alone and light deprivation in combination with exogenously administered melatonin indicated significant neuroprotective effects. Although there may be other important pathways, darkness-induced elevation in endogenous melatonin secretion appears to play an important role in this neuroprotective outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, it is possible that the pineal gland sustained damage due to the relatively uncontrolled nature of the weight-drop injury compared to the CCI. Additionally, some authors report MEL administered during night hours, while endogenous MEL levels are high, was effective whereas administration during daylight hours was not [25, 27]. More research into the pharmacology and pharmacokinetics of these compounds following the CCI and other TBI models would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that the pineal gland sustained damage due to the relatively uncontrolled nature of the weight-drop injury compared to the CCI. Additionally, some authors report MEL administered during night hours, while endogenous MEL levels are high, was effective whereas administration during daylight hours was not [25, 27]. More research into the pharmacology and pharmacokinetics of these compounds following the CCI and other TBI models would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is also involved in the regulation of other systems such as the pain system. In fact, the antinociceptive effect of melatonin has been demonstrated in animal models of acute pain (Li et al 2005;Ucar et al 2005;Elmegeed et al 2007), inflammatory pain (Arreola-Espino et al 2007), and neuropathic pain (Ulugol et al 2006). Preliminary studies in humans have shown melatonin effects on some pain syndromes, especially fibromyalgia (Citera et al 2000) and acute postoperative pain (Acil et al 2004;Caumo et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…There is a dearth of research on improving sleep and reversing the negative effects of sleep disruption on homeostasis in critically‐ill patients. Melatonin is an agent with the capacity of entraining of circadian rhythms (chronobiotic effect) as well as having anti‐insomnia effects and neuroprotective actions [3, 73]. These actions have been demonstrated in humans by clinical trials and in experimental animal models [71, 74].…”
Section: Craniocerebral Trauma and Sleepmentioning
confidence: 99%
“…(c) CCT reportedly alters endogenous pineal melatonin secretion during the acute post‐traumatic period. These disturbances are characterized by the absence of the normal melatonin circadian rhythm [3, 71]. In addition to its protective action as an antioxidant in the brain, the general opinion is that melatonin is also a synchronizer of circadian rhythms [107].…”
Section: Benefits Of Melatonin In the Therapeutic Treatment Of Patienmentioning
confidence: 99%
See 1 more Smart Citation